Phonology, Morphology, and Sound Symbolism in the First Pokémon Generation - Budi Rahmat Setiawan; Tatang Hariri (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Linguistics is unconsciously used in naming. Many human creativity in naming were done by applying linguistic theories. The study explores how Pokémon names were created based on linguistic theories. It is because more new names and terminologies have always been created following the development of technology and human civilizations. Literary works are one of human creativity that never ends. As a result, many new words are coined to be distinctive and memorable for the ‘market’. For thirty years, Pokémon has always updated their creativity in naming thousands of terminologies and Pokémon species. It makes scholars intrigued in understanding human capability in applying linguistic theories on forming their names. Phonological, graphemical as well as morphological theories were used in forming new Pokémon names. This is a descriptive-qualitative research. Data used were obtained from a webpage named Pokémon database. The data used in this research were limited to the first generation of the Pokémon game names. The research is expected to bring new horizons as the results of how Pokémon names were created. The results show that there are additional ways of naming literary characters phonologically and morphologically. The result shows consonant insertion and vowel deletion in addition to Balteiro’s (2013) theory and suffixation in addition to Mattielo’s (2013) theory used in forming Pokémon names. There is also certain sound used in order to create an archaic effect such as the ending -th.